Quality improvement collaborative aiming for Proactive HEAlthcare of Older People in Care Homes (PEACH): a realist evaluation protocol. Issue 11 (12th November 2018) - Devi, Reena; Meyer, Julienne; Banerjee, Jay; Goodman, Claire; Gladman, John Raymond Fletcher; Dening, Tom; Chadborn, Neil; Hinsliff-Smith, Kathryn; Long, Annabelle; Usman, Adeela; Housley, Gemma; Bowman, Clive; et al.
Abstract : Introduction: This protocol describes a study of a quality improvement collaborative (QIC) to support implementation and delivery of comprehensive geriatric assessment (CGA) in UK care homes. The QIC will be formed of health and social care professionals working in and with care homes and will be supported by clinical, quality improvement and research specialists. QIC participants will receive quality improvement training using the Model for Improvement. An appreciative approach to working with care homes will be encouraged through facilitated shared learning events, quality improvement coaching and assistance with project evaluation. Methods and analysis: The QIC will be delivered across a range of partnering organisations which plan, deliver and evaluate health services for care home residents in four local areas of one geographical region. A realist evaluation framework will be used to develop a programme theory informing how QICs are thought to work, for whom and in what ways when used to implement and deliver CGA in care homes. Data collection will involve participant observations of the QIC over 18 months, and interviews/focus groups with QIC participants to iteratively define, refine, test or refute the programme theory. Two researchers will analyse field notes, and interview/focus group transcripts, coding data using inductive and deductive analysis. The key findings and linked programme theory will be summarised as context-mechanism-outcome configurations describing what needs to be in place to use QICs to implement service improvements in care homes. Ethics and dissemination: The study protocol was reviewed by the National Health Service Health Research Authority (London Bromley research ethics committee reference: 205840) and the University of Nottingham (reference: LT07092016) ethics committees. Both determined that the Proactive HEAlthcare of Older People in Care Homes study was a service and quality improvement initiative. Findings will be shared nationally and internationally through conference presentations, publication in peer-reviewed journals, a graphical illustration and a dissemination video.